PERAN TANAMAN SEBAGAI INSEKTISIDA NABATI TERHADAP GIGITAN NYAMUK Aedes aegypt VEKTOR DEMAM BERDARAH DENGUE - Iqbal Elka Putra, Fuad (Essence of Scientific Medical Journal; Vol 18 No 2 (2020): Volume 18 No. 2 (Juli - Desember 2020) Essential: Essence of Scientific Medical Journal, 2021)
Introduction : Dengue hemorrhagic fever (DHF) caused by the female dengue virus Aedes aegypt causes nearly 390 million people to be infected each year. the number of dengue cases is increasing from year to year and extraordinary events (KLB) tend to occur every 5 years. Vector mosquito control still uses chemical insecticides, so alternative insecticides such as plant-based insecticides from plants that are cheap, easy to obtain, environmentally friendly and effective in killing adult mosquitoes are needed. Discussion : Test repelens of some plant extracts are at a dose of 100% which is able to reject mosquito bites above 80% per hour including leaf extracts of Zodia linalol and apinene as mosquito repellent fluids. Tobacco leaf extract is able to resist for 3 hours with the active substances of nicotine and alkaloid tobacco leaves. Gondopuro leaf extract is able to resist for 1 hour containing saponins. Serai Wangi leaf extract can resist for 2 hours because it contains geraniol, citronellol, citronellal, and citral. Clove leaf extract was able to resist for 4 hours as much as 81.7%. Chrysanthemum flower extract was able to resist for 1 hour as much as 89.6%, while suren leaf extract, tuba root and lavender were only able to resist Aedes aegypti mosquito bites below 80%. Conclusion : Plants can be plant-based insecticides and are proven effective in preventing Aedes aegypt mosquito vector bites   Keywords : Aedes aegypt , dengue hemorrhagic fever, plant insecticide